2010
DOI: 10.1111/j.1469-0691.2009.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Personalized management of patients with inoperable alveolar echinococcosis undergoing treatment with albendazole: usefulness of positron-emission-tomography combined with serological and computed tomography follow-up

Abstract: The present study aimed to identify a sub-group of inoperable alveolar echinococcosis (AE) patients undergoing long-term treatment with benzimidazole (BZM) who presented with an evolution suggestive of a parasitocidal effect. An evolution compatible with parasite death was observed in five patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…Previous studies have demonstrated the value of standard 18 F-FDG PET in the follow-up of patients with AE, and this imaging procedure is currently considered the best surrogate marker of parasite viability. It has especially been proposed for the detection of patients in whom the parasite had become inactive and in whom treatment interruption could be programmed (7,8,(10)(11)(12)22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the value of standard 18 F-FDG PET in the follow-up of patients with AE, and this imaging procedure is currently considered the best surrogate marker of parasite viability. It has especially been proposed for the detection of patients in whom the parasite had become inactive and in whom treatment interruption could be programmed (7,8,(10)(11)(12)22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to WHO IWGE expert consensus (5), all patients underwent a separate ultrasound examination as a routine imaging technique, as well as multiphase CT or MR imaging, as a part of combined follow-up (22,23) when other tests suggested that disease-or treatment-related complications were present. However, as stated by the WHO IWGE expert consensus, the results of CT or MR imaging were not taken into consideration when decisions on treatment interruption were being made (5).…”
Section: Biologic and Serologic Testsmentioning
confidence: 99%
“…Benzimidazoles (mebendazole and albendazole) are parasitostatic drugs that can be used against parasitic metacestodes (2,12,16). Although benzimidazoles are widely regarded as parasitostatic, it has been reported that they may, in some cases, exert parasiticidal effect and thus the treatment may be safely terminated after some time (37,40). On the other hand, these drugs have some side effects and are potentially teratogenic.…”
Section: Treatment and The Role Of Interventional Radiologymentioning
confidence: 99%
“…In contrast, 18F-fluorodeoxyglucose (FDG)-PET is suggested to show the viability and metabolic activity in AE lesions (16,36,37). An increased FDG uptake is observed in neoplastic and inflammatory-infectious lesions.…”
Section: Pet-ctmentioning
confidence: 99%
See 1 more Smart Citation